Genetic Counseling for Bladder Exstrophy-Epispadias Complex - Reutter, Heiko Martin; Holmdahl, Gundela (European Journal of Pediatric Surgery, 2021)
Bladder exstrophy-epispadias complex (BEEC) represents the severe end of the uro-rectal malformation spectrum and has profound impact on continence, sexual, and renal function. Treatment of BEEC is primarily surgical, and the main goals are safe closure of the abdominal wall, urinary continence while preserving renal function, and adequate cosmetic and functional genital reconstruction. Psychosocial and psychosexual outcomes and adequate health-related quality of life depend on long-term multidisciplinary care. The overall outcome is now considered very positive and affected individuals usually lead self-determined and independent lives with the desire to start their own families later in life. Certainty about the risk of recurrence and the provision of information about the current state of knowledge about the identified genetic causes with high penetrance will have an impact on family planning for healthy parents with an affected child and for affected individuals themselves. This review addresses this information and presents the current state of knowledge.
CRIS-Team WoS Importer:2021-12-31